SYNTHESIS ON THE NI-P MATERIAL - Minodora-Maria PASARE; Radostin DIMITROV (Fiabilitate şi Durabilitate)
Due to their properties, new materials are widely used in industry. The procedures for making these types of materials and their internal structure, lead to obtaining special characteristics. This paper presents a brief characterization of the Ni-P type material in terms of its production processes, properties and applications in industry.